PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA GURU PADA SMK â€œXYâ€ KOTA PEKANBARU - Dewita, Riska Afriani; Yapentra, Arhipen (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
This article is the result of co-research the author and students in completing her final education at STIE Riau. The purpose of this research is to study and analyze influence of Supervision toward the Work Discipline of Teachers in the Vocational High School